Effect of Diffusion and Modulated Frequency in an Ion-Implanted OPFET - Singh V.K.; Pal B.B. (My University, 2025)
Studies have been made on the effect of diffusion and modulated frequencies in an ion-implanted Si photo MESFET (OPFET). It is observed that for a particular radiation flux density and absorption coefficient, the device characteristics (I–V), threshold voltage (VT), and intrinsic device parameters (Cgs, Rds, etc.) change only at millimeter wave frequencies. When the effect of diffusion is ignored, the modulated frequency alone also changes these terminal properties of the OPFET at millimeter-wave frequencies, but then the changes are more prominent. The diffusion simply reduces these effects. Copyright © 1987 by The Institute of Electrical and Electronics Engineers, Inc.